SOCIO-PSYCHOLOGICAL POTENTIAL OF PERSONALITY IN THE XXI CENTURY - Kondratyuk Н.В. (Pedagogy of Higher and Secondary Education, 2022)
The article is directed on opening of concept socially - psychological potential and his components, and also influence of the last on development and functioning of personality in youth age. During research we proved that conponents socially - psychological potential, such as system of values, co-operation with other people, ability to subordinate the conduct to the requirements of situation, responsibility for own life, expansion of social connections, orientation, on the future, acquisition of social knowledges definitely influence on personality; than higher level of development socially - psychological potential of senior pupil, that consciousress and there more effective is development of his personality.